Photoelectrocatalytic application of palladium decorated zinc oxide-expanded graphite electrode for the removal of 4-nitrophenol: experimental and computational studies. Issue 19 (13th March 2018) - Umukoro, Eseoghene H.; Peleyeju, Moses G.; Idris, Azeez O.; Ngila, Jane C.; Mabuba, Nonhlangabezo; Rhyman, Lydia; Ramasami, Ponnadurai; Arotiba, Omotayo A.
Abstract : Band diagram for the mechanism of charge transfer involved in the photo-electrocatalytic degradation activity of Pd-ZnO-expanded graphite (EG) photoanode on 4-nitrophenol removal. Abstract : A novel Pd–ZnO-expanded graphite (EG) photoelectrode was constructed from a Pd–ZnO-EG nanocomposite synthesised by a hydrothermal method and characterised using various techniques such as X-ray diffractometry (XRD), Raman spectroscopy, UV-Vis diffuse reflectance spectroscopy, nitrogen adsorption–desorption analysis, transmission electron microscopy (TEM), scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS). Cyclic voltammetry and photocurrent response measurements were also carried out on the electrode. The Pd–ZnO-EG electrode was employed in the photoelectrocatalytic removal of 4-nitrophenol as a target water pollutant at a neutral pH and with a current density of 7 mA cm −2 . Optical studies revealed that the Pd–ZnO-EG absorbed strongly in the visible light region. The Pd–ZnO-EG electrode showed improved photoelectrocatalytic activity in relation to ZnO-EG and EG electrodes for the removal of the 4-nitrophenol. The photocurrent responses showed that the Pd–ZnO-EG nanocomposite electrode could be employed as a good photoelectrode for photoelectrocatalytic processes and environmental remediation such as treatment of industrial waste waters. Density functional theory method was used to model the oxidative degradation of 4-nitrophenol by the hydroxyl radical which generates hydroquinone, benzoquinone, 4-nitrocatechol, 4-nitroresorcinol and the opening of the 4-nitrophenol ring. Furthermore, the hydroxyl radical is regenerated and can further oxidise the ring structure and initiate a new degradation process.